The form of the sacrament of baptism in the light of the document of the Congregation for the Doctrine of the Faith of June 24, 2020 - Janczewski, Zbigniew (Prawo Kanoniczne, 2023)
During the celebration of the sacrament of baptism, like the others, for their validity, it is necessary to use the prescribed matter and form. The following presentation discusses the form of the celebration of baptism, with particular emphasis on the last document concerning it, issued by the Holy See. The article consists of three parts. The first part the introductory issues in order to provide an appropriate research perspective, i.e. the responsibility of the Holy See for the administration of the sacraments and the form of the sacraments and its influence on the validity of administering them. The next part is an analysis of documents relating to the importance of the form of baptism in the historical context. The last one contains an analysis of the 2020 document of the Congregation for the Doctrine of the Faith Responses to questions proposed on the validity of Baptism conferred with the formula „We baptise you in the name of the Father and of the Son and of the Holy Spirit”.